A variedade léxica da língua espanhola em dicionários bilíngues espanhol-português para aprendizes brasileiros - Artico, Jéssica Aparecida; Nadin, Odair Luiz [UNESP] (Universidade Estadual de Maringa, 2011)
Due to factors such as globalization and the demography of Hispanic countries, the Spanish language has influenced worldwide, especially since the last decade of the 20th century, mainly countries which are geographically close to Spanish American countries, such as Brazil. In this context, it is necessary to think of the linguistic variation of the Spanish language, in which we emphasize the lexical variation. As any language, Spanish has a colossal and wealthy lexicon with different varieties related to the characteristics from each region: history, culture, customs etc. This diversity influences the development, the amplification and the renewal of a language, as well as the teaching-learning process. Thus, we proposed to analyze the lexicon varieties of Spanish language entries in some Spanish-Portuguese bilingual dictionaries for Brazilian learners. In order to achieve this goal, we selected some examples of lexical variety in a corpus organized with texts of different textual genres and we verified if these lexical items are registered in the dictionaries chosen. As the corpus is organized from texts present in didactic manuals used in Brazil, our goal is to verify if the vocabulary which the Brazilian learner has contact in formal education is registered in the analyzed dictionaries.
The lexical variety of Spanish language in Spanish-Portuguese bilingual dictionaries for Brazilian learners
Keywords: Bilingual dictionary; Lexical variation; Spanish language